Experimental study of radio frequency waves resonant transmission through a semiconductor plasma sheet with supercritical electron density. (28th July 2022) - Bogatskaya, A V; Klenov, N V; Popov, A M; Schegolev, A E; Titovets, P A; Tereshonok, M V
Abstract: We present an experimental study of the effect of resonant tunnelling of radio frequency signals through a silicon semiconductor plasma sheet with supercritical electron density. The resonance effect appears when a dielectric plate is placed behind the plasma sheet and is determined by the dielectric parameters. The numerical modelling of the effect under the experimental conditions was implemented and compared with the experimental data. The features of the wave resonant tunnelling effect in the case of a high-collisional semiconductor plasma were analyzed. This study confirms the proposed earlier method of overcoming the radiocommunication blackout problem.